Impact of volcanic stratospheric aerosols on diurnal temperature range in Europe over the past 200 years: Observations versus model simulations. Issue 16 (30th August 2013) - Auchmann, Renate; Arfeuille, Florian; Wegmann, Martin; Franke, Jörg; Barriendos, Mariano; Prohom, Marc; Sanchez‐Lorenzo, Arturo; Bhend, Jonas; Wild, Martin; Folini, Doris; Štěpánek, Petr; Brönnimann, Stefan
Abstract: [1] We analyze the impact of stratospheric volcanic aerosols on the diurnal temperature range (DTR) over Europe using long‐term subdaily station records. We compare the results with a 28‐member ensemble of European Centre/Hamburg version 5.4 (ECHAM5.4) general circulation model simulations. Eight stratospheric volcanic eruptions during the instrumental period are investigated. Seasonal all‐ and clear‐sky DTR anomalies are compared with contemporary (approximately 20 year) reference periods. Clear sky is used to eliminate cloud effects and better estimate the signal from the direct radiative forcing of the volcanic aerosols. We do not find a consistent effect of stratospheric aerosols on all‐sky DTR. For clear skies, we find average DTR anomalies of −0.08°C (−0.13°C) in the observations (in the model), with the largest effect in the second winter after the eruption. Although the clear‐sky DTR anomalies from different stations, volcanic eruptions, and seasons show heterogeneous signals in terms of order of magnitude and sign, the significantly negative DTR anomalies (e.g., after the Tambora eruption) are qualitatively consistent with other studies. Referencing with clear‐sky DTR anomalies to the radiative forcing from stratospheric volcanic eruptions, we find the resulting sensitivity to be of the same order of magnitude as previously published estimates for tropospheric aerosols during the so‐called "global dimming" period (i.e., 1950s to 1980s). Analyzing cloud cover changes after volcanic eruptions reveals an increase in clear‐sky days in both data sets. Quantifying the impact of stratospheric volcanic eruptions on clear‐sky DTR over Europe provides valuable information for the study of the radiative effect of stratospheric aerosols and for geo‐engineering purposes. Key Points: Comprehensive study on the effect of volcanic forcing on daily temperature range Major volcanic eruption since 1800 studied in observation and model data Analysis of clear‐sky days to quantify the response to radiative forcing